Dossier : immigranten-gastarbeiders met hun en onze problemen - Bundervoet, Frank; Haex, J.; Leman, Johan (Leuven: Kultuurleven, 1976)
"Medewerkers: F. Bundervoet, J. Haex, J. Leman... et al. Themanummer Kultuurleven"